Physical violence against healthcare workers employed at a local health unit in the Lazio Region, Italy: A cross-sectional study - Angelo SACCO (GIornale Italiano di Psicologia e Medicina del Lavoro, 2022)
Introduction: This study aimed to study the prevalence of physical attacks against healthcare workers (HCWs) employed at a local health company, in the Lazio region, Italy. Methods: A cross-sectional study was carried out among HCWs employed at public hospitals (n=3) and outpatient care services (n=4). Data was elaborated by the occupational physicians of the company in the context of occupational health surveillance, which is mandatory in Italy, in the period 2010 – 2014. Descriptive statistics (frequency and percentage) of workplace accidents -collected by health and safety managers of the company- were reported. Results: A total of 22 workplace accidents were caused by physical assaults, of which 11 (50%) involved male operators. The average age of the victims was 47.9+9.4 years. Assaults were concentrated in the hospitals (19 of the 22 attacks) and involved nurses (n=12, 54.5%), doctors (n=6, 27.3%), auxiliaries (n=2, 9.1%), and office workers (n=2, 9.1%). Most cases (n=20) were acted by patients, in emergency departments (n=10, 45.4%), and in psychiatric (n=6, 23.3%) and mental health centers (n=2, 9.1%). Discussion: Our findings confirm results from the scientific literature, as well as recommendations from national and international guidelines. A procedure for WV prevention and management in the healthcare setting is needed. Occupational stakeholders should address the underreporting phenomenon and carry out a combination of structural, organizational, and training measures.